Incidence and characteristics of kitesurfer injuries. DOI: 10.5007/1980-0037.2011v13n3p195 - Joscelito de Oliveira Berneira; Marlos Rodrigues Domingues; Marina Arejano de Medeiros; César Augusto Otero Vaghetti (Universidade Federal de Santa Catarina, 2011)
Kitesurfing is a new sport and consists of a combination of surf, windsurf and wakeboard. Its main characteristics are the relationship with wind speed and direction and the high rate of injuries. The aim of this study was to determine the type, body region, and etiological agent of injuries in kitesurfers from the towns of Pelotas and Rio Grande, RS. A sample of 50 kitesurfers (mean age: 30.7 ± 7.9 years, height: 175.9 ± 6.6 cm, body weight: 79.4 ± 11.5 kg, and practice time: 4.2 ± 2.7 years) was studied. A questionnaire with open and closed questions was used for data collection. Seventy-three injuries were identified in all participants and most of them had more than one type of injury. Sprain was the most frequent type of injury (35.6%) and the lower limbs were the most affected (50.7%). The maneuver was the etiological agent that caused most injuries (57.5%). This study suggests proprioceptive exercise to increase the power of muscle recruitment in extreme situations; stretch training especially of the trunk and lower limbs, the sites most affected by injuries, and global workout to increase muscle endurance.